Numerical simulation and experimental research on combustion characteristics of compression-ignition engine under an O2/CO2 atmosphere. Issue 3 (3rd July 2017) - Chen, Hanyu; Shen, Hai; Wu, Tong; Zuo, Chengji
ABSTRACT: This study investigates the combustion characteristics of compression-ignition engines under an O2 /CO2 atmosphere, through numerical simulation and experimental analysis methods, which will eventually provide a new solution of the "NOx-Soot" trade-off problem. The computational fluid dynamics (CFD) software FIRE is adopted to simulate in-cylinder combustion temperature and pressure, according to different O2 volume ratio and different ignition advance angle. The dyno test including visualisation diagnostic is carried out under the above gas composition so that the emission and combustion characteristics can be analysed. The simulation results of engine power performance show that when the ignition advance angle remains unchanged compared to the baseline engine, a combination of 65% O2 with 35% CO2 is the recommended gas composition. And the in-cylinder peak pressure of the engine is about 6.66 MPa, which is equivalent to that when the engine runs at normal air intake conditions. The results of the optical engine experiment show that, compared to the baseline engine under normal air, the ignition timing, the timing of maximum rate of pressure rise, the timing of maximum rate of heat release and peak pressure are 0.66°CA, 4.93°CA, 5°CA and 0.15°CA ahead, respectively.